Desenvolvimento de um sistema de caracterização térmica de materiais por efeito fotoacústico - Possamai, Leandro Mendes (2017)
The photoacoustic effect was first reported by Alexander Graham Bell in 1880. Bell realized that when a solid placed in a chamber was irradiated with light modulated, occurred the propagation of sound waves that could be heard through a tube connected to the chamber. Because the technology available at the time was insufficient to quantify the magnitude of sound waves, this process did not receive much attention. However, with the advent of the microphone in 1938- which made it possible the rapid and effective detection of sound waves-the interest in this process increased. Initially, this effect was studied in gases and, later, in the 1970s, it was used in the investigation of the properties of solid materials through photoacoustic spectroscopy (EFA). Currently, EFA is applied in physics, chemistry, biology, engineering and medicine. The objective of this work was to assembly a system of open cell photoacoustic measurements for the thermal characterization of materials. For this, an experimental arrangement was built up that has as sensor element a low cost commercial electret microphone. Tests have shown that the system is feasible for the investigation of the thermal properties of materials.